Математические журналы и их интернационализация: первый португальский журнал “Jornal de sciencias mathematicas e astronomicas” - Kharlamova, Vera I. (2016)
The article describes the historical place of the first Portuguese Journal “Jornal de sciencias mathematicas e astronómicas” (Teixeira´s Journal) during the development of the European mathematical community at the end of the 19th century.